The effect of arm-crank exercise training on power output, spirometric and cardiac function and level of autonomy in persons with tetraplegia. Issue 7 (8th August 2020) - Brizuela, G.; Sinz, S.; Aranda, R.; Martínez-Navarro, I.
Abstract: Studies on the effects of exercise training in persons with cervical spinal cord injury (CSCI) are scarce. The aim of this study was to determine the effect of an 8-week stationary arm-crank exercise (ACE) training programme on the level of autonomy, exercise performance, pulmonary functional parameters and resting heart rate variability (HRV) in persons with CSCI. Quadriplegia Index of Function (QIF), arm-crank peak power output (Ppeak), spirometric variables, and HRV indices were measured before and after the training programme in a group of 11 persons with CSCI. ACE training increased Ppeak in both groups ( p < 0.05), whereas maximum voluntary ventilation (MVV) and low frequency HRV (LF) improved only in the lower CSCI group ( p < 0.05). Moreover, QIF and Ppeak were significantly correlated before ( r = 0.88; p < 0.01) and after ( r = 0.86; p < 0.01) the training period. However, no significant changes were found in the level of autonomy (QIF) as a result of the intervention. Therefore, stationary ACE training appears to be a feasible and effective method for aerobic exercise in persons with tetraplegia and a short-term intervention is able to significantly improve exercise capacity, cardiac autonomic regulation and respiratory muscle endurance, regardless of the absence of significant immediate changes in the level of autonomy.